Concepts and Relations in Neurally Inspired In Situ Concept-Based Computing - van der Velde, Frank (Frontiers in Neurorobotics, 2016)
In situ concept(-based) computing is based on the notion that conceptual representations in the human brain are ‘in situ’. In this way, they are grounded in perception and action. Examples are neuronal assemblies, whose connection structures develop over time and are distributed over different brain areas. In situ concepts representations cannot be copied or duplicated because that will disrupt their connection structure, and thus the meaning of these concepts. Higher-level cognitive processes, as found in language and reasoning, can be performed with in situ concepts by embedding them in specialized neurally-inspired ‘blackboards’. The interactions between the in situ concepts and the blackboards form the basis for In situ concept computing architectures. In these architectures memory (concepts) and processing are interwoven, in contrast with the separation between memory and processing found in Von Neumann architectures. Because the further development of Von Neumann computing (more, faster, yet power limited) is questionable, in situ concept computing might be an alternative for concept based computing. In situ concept computing will be illustrated with a recently developed BABI reasoning task. Neurorobotics can play an important role in the development of in situ concept computing because of the development of in situ concept representations derived in scenarios as needed for reasoning tasks. Neurorobotics would also benefit from power limited and in situ concept computing.